Correlation between expression of p53, p21/WAF1, and MDM2 proteins and their prognostic significance in primary hepatocellular carcinoma - Zhang, Mei-Fang (BioMed Central, 2009)
BACKGROUND: Tumor Protein p53 (p53), cyclin-dependent kinase inhibitor 1A (p21/WAF1), and murine double minute 2 (MDM2) participate in the regulation of cell growth. Altered expression of these gene products has been found in malignant tumors and has been associated with poor prognosis. Our aim was to investigate the expression of the 3 proteins in hepatocellular carcinoma (HCC) and their prognostic significance. METHODS: We examined p53, p21/WAF1, and MDM2 expression in 181 pairs of HCC tissues and the adjacent hepatic tissues by performing immunohistochemistry and examined the expression of the 3 proteins in 7 pairs of HCC tissues and the adjacent hepatic tissues by using western blot analysis. RESULTS: The expression of p53, p21/WAF1, and MDM2 in the HCC tissues was significantly higher than those in the adjacent hepatic tissues (P < 0.05). A statistical correlation was observed between p53 and p21/WAF1 expression in HCC tissues (R = 0.195, P = 0.008). A statistical correlation was observed between expression of p53 and p21/WAF1 (R = 0.380, P = 0.000), p53 and MDM2 (R = 0.299, P = 0.000), p21/WAF1 and MDM2 (R = 0.285, P = 0.000) in 181 liver tissues adjacent to the tumor. Patients with a low pathologic grade HCC (I+II) had a higher tendency to express p53 on tumor cells than the patients with high pathologic grade HCC (III+IV) (P = 0.007). Survival analysis showed that positive p21/WAF1 expression or/and negative MDM2 expression in HCC was a predictor of better survival of patients after tumor resection (P < 0.05). CONCLUSIONS: The proteins p53, p21/WAF1, and MDM2 were overexpressed in all the HCC cases in this study, and p53 and p21/WAF1 overexpression were positively correlated. The expression of p21/WAF1 and MDM2 can be considered as 2 useful indicators for predicting the prognosis of HCC.